Use of the essential nutrition actions framework improved child growth in Bangladesh - Waid, Jillian (Maternal & child nutrition, 2019)
The Essential Nutrition Actions (ENA) framework is an evidence-based set of cost-effective, integrated tools for training health and community workers to promote optimal nutrition practices for the first 1,000 days. This ENA pilot project (ENAPP) was implemented with United States Agency for International Development (USAID) funding from August 2008 to September 2009 in six unions of the working area of an existing USAID-funded, Title II programme in southern Bangladesh. ENAPP, which targeted governmental and non-governmental service providers, was intended to strengthen the behaviour change component of the nutrition strategy of this project. Following a qualitative review of ENAPP's activities, this evaluation uses administrative (growth monitoring) data and propensity score matching of pre-intervention characteristics to create multiple counterfactuals for difference-in-difference estimations of the impact of ENAPP on child nutritional status. Records indicated that government and community healthcare workers received intensive training, and these staff reported that they could effectively integrate ENA messages into their existing responsibilities. Both longitudinal and cross-sectional analyses indicate that ENAPP was successful in increasing children's weight-for-age z-scores, and the difference in z-scores between the treatment and the comparison group increased with time. The materials and methods used in this pilot project should be scaled up, based on the success of these tools and the project's ability to link with and influence the local health system.
First published: 11 September 2018
Gesehen am 23.04.2019